Fidedignidade de instrumento para avaliação da qualidade do acolhimento com classificação de risco - Bellucci Júnior, José Aparecido (2016)
The evaluation of quality in Emergency Hospital Services is necessary for the development and safety of care, because by assigning values to practice, it is possible to punctuate the areas of internal systems that require administrative interventions. In this regard, the evaluation through the use of validated and reliable instruments is important for diagnosing the failures and guiding the processes of changes to the quality of care. The present study had as a General Objective, To Test the Trust of the Instrument of Evaluation of the Quality of the User Embracement with Risk Rating (UERR) in Emergency Hospital Services. In order to contextualize and subsidize the discussion on the subject, an Integrative Literature Review was carried out, through which data were obtained regarding the results of the implementation of the User Embracement with Risk Rating in Emergency Hospital Services in Brazill, in institutions that implemented this system in the period 2004-2013. We searched the LILACS, SciELO, BDENF, MEDLINE and ColecionaSUS databases for the period 2004-2013. In the 13 articles selected, the studies were categorized according to the Donabedian dimensions of health evaluation, Structure, Process and Outcome. It was found that the main advances of the UERR are attributed to the improvements in the security and environment of the services (Structure); Autonomy of the nurse in the handling of cases, strengthening of links between professionals and users, flow of care and organization of services (Process); Reduction of outpatient demand, user satisfaction, humanization and prioritization of severe cases (Outcome). Regarding the challenges, they highlighted the failures in the implementation of the UERR and in the physical space (Structure); Risk classification performed by technicians and; Little effectiveness in referencing with the Basic Health Network (Process). Subsequently, the Instrument for Evaluation User Embracement with Risk Rating in Hospital Emergency Services was developed, previously built and validated by the Content Validation Technique. The quantitative methodological study was carried out through the application of three Reliability Tests and Appearance Validation. The instrument was applied to 497 workers of the Nursing and Reception teams of five Emergency Hospital Services. For the reliability analysis, the coefficient Alfha (?) of Cronbach, the item / total correlation and the factorial analysis were calculated. The first reliability test obtained Alfron (?) from Cronbach 0.56; The second 0.49 and the third 0.76. After the third test, items 07 and 09 of the initial instrument were removed and; The final Cronbach Alfha (?) resulted in 0.79. Factor analysis resulted in a notorious division of data into three factors, with high factor loads, confirming the three dimensions of health assessment in which the instrument was constructed: Structure, Process and Result. The instrument achieved a high degree of reliability and; The final version is presented as a Likert type scale, with 19 items and five response levels. It was concluded that the instrument tested shows stability and consistency among all its internal components and this allows its safe use in processes that evaluate the quality of User Embracement with Risk Rating, implanted in any Emergency Hospital Service in Brazil